THE EFFECT OF ADVERTISING, PRICE PERCEPTION, AND PRODUCT QUALITY ON CUSTOMER SATISFACTION - Ali, Mukti; Kurniawan, Rendi (Ecopreneur.12, 2024)
This research aims to determine the influence of advertising, price, and product quality on customer satisfaction in Mezale Snack's banana chips. The research utilized a questionnaire for data collection, targeting the customer population of Mezale Snack. As the exact population size was unknown, the sample size was determined using the Cochran formula, resulting in 97 respondents. The data analysis method employed in this research was quantitative analysis using SPSS 22.0 for Windows. The research findings indicate that advertising has a positive and significant influence on customer satisfaction. Price has a positive and significant influence on customer satisfaction. Product quality has a positive and significant influence on customer satisfaction. All three independent variables, namely advertising, price, and product quality, have a positive and significant influence on customer satisfaction. These three independent variables, namely advertising, price, and product quality, can explain 31.5% of the changes in customer satisfaction.